2020
DOI: 10.3390/polym12040833
|View full text |Cite
|
Sign up to set email alerts
|

Highly Hydrophobic Cotton Fabrics Modified by Poly(methylhydrogen)siloxane and Fluorinated Olefin: Characterization and Applications

Abstract: Highly hydrophobic cotton fabrics were obtained with poly(methylhydrogen)siloxane (PMHS) and a further fluorinated olefin modification. The chemical structures and microstructures of PMHS-modified cotton fabrics were characterized, and application of the resultant cotton fabrics in stain resistance and oil–water separation was demonstrated. PMHS chains with very low surface energy were grafted onto cotton fabric by the dehydrogenation reaction between –Si–H of PMHS and –OH groups of cotton fabric at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Regarding the specific surface treatment of NPs with polymethylhydrogensiloxane (MHX), through consideration of its molecular structure (i.e., a dimethyl silicone withsome methyl radicals replaced by hydrogen), each chain contained amounts of ≡Si–H (silicon hydride) and –CH 3 (methyl) groups. Therefore, as suggested in Scheme 1 , MHX was able to react at the sites of hydrogen atoms (≡Si–H) via a dehydrogenation reaction with the participation of the hydroxyl groups (–OH) present at the surface of MNPs or of other different materials (e.g., glass, leather, fabric surfaces, cellulose derivatives, and fillers such as SiO 2 ), finally resulting in the covalent linkage of hydrophobic chains (MHX) onto the different substrates [ 65 , 66 ]. Moreover, the layers of MHX formed at the surface of MNPs could be cured by heating in the presence or absence of catalysts, with beneficial effects through developing water repellency.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the specific surface treatment of NPs with polymethylhydrogensiloxane (MHX), through consideration of its molecular structure (i.e., a dimethyl silicone withsome methyl radicals replaced by hydrogen), each chain contained amounts of ≡Si–H (silicon hydride) and –CH 3 (methyl) groups. Therefore, as suggested in Scheme 1 , MHX was able to react at the sites of hydrogen atoms (≡Si–H) via a dehydrogenation reaction with the participation of the hydroxyl groups (–OH) present at the surface of MNPs or of other different materials (e.g., glass, leather, fabric surfaces, cellulose derivatives, and fillers such as SiO 2 ), finally resulting in the covalent linkage of hydrophobic chains (MHX) onto the different substrates [ 65 , 66 ]. Moreover, the layers of MHX formed at the surface of MNPs could be cured by heating in the presence or absence of catalysts, with beneficial effects through developing water repellency.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, when this cotton ber is immersed in a non-aqueous solvent containing a Karstedt catalyst, this superhydrophobic property can be preserved for a long time. 40 As shown in Fig. S5, † the cotton bers treated by this method can still maintain super hydrophobic ability aer 4 consecutive soaping treatments.…”
Section: Resultsmentioning
confidence: 88%
“…The modification of the blended sponge with POSS is based on the interaction between the POSS molecule and the hydroxyl groups in lignin, which was proven by the disappearance of the peaks of hydroxyl groups in the range of 3400–3600 cm −1 . This indicated that lignin and POSS were successfully incorporated into the composites [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%